Feasibility assessment: A cycloidal rotor to replace conventional helicopter technology - Gagnon, L.; Morandini, M.; Quaranta, G.; Muscarello, V.; Masarati, P.; Bindolino, G.; Xisto, C.; Pascoa, J.C. (My University, 2014)
A mathematical model is presented for the solution of the aerodynamic performances of a cycloidal rotor. It is solved algebraically for the cases where the forces and incoming wind velocity share the same direction. The model is validated against experimental data coming from three different sources. It is then used to evaluate the viability of using a cycloidal rotor as a replacement for the traditional tail rotor of a helicopter. By doing so, power is saved by the helicopter having non-null advance ratios. The savings reach 50% at an advance ratio of 0.33. It was found that imposing a constant cycloidal rotor angular velocity does not reduce the efficiency and that high pitch angles are the most efficient. The experimental data indicates that three dimensional effects have an influence on the cycloidal rotor performance. A three dimensional Euler fluid dynamic analysis confirms the experimental findings.